2010
DOI: 10.1016/j.rbmo.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of aneuploid blastocysts using a new 12-chromosome FISH test

Abstract: Fluorescence in-situ hybridization (FISH) has been the principal method used for the identification and preferential transfer of chromosomally normal embryos, in the context of both preimplantation genetic diagnosis (PGD) and screening (PGS). Generally, the probe combinations used during PGS have focused on chromosomes frequently identified as abnormal in prenatal samples or material derived from first-trimester spontaneous abortions. Recent data, however, obtained with the use of comparative genomic hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
0
31
0
2
Order By: Relevance
“…Aneuploid embryos often demonstrate multiple chromosomal defects. Linkages between different chromosomes, therefore, were believed to detect most chromosomally abnormal embryos, even when assessing only limited chromosome numbers [25,26].…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Aneuploid embryos often demonstrate multiple chromosomal defects. Linkages between different chromosomes, therefore, were believed to detect most chromosomally abnormal embryos, even when assessing only limited chromosome numbers [25,26].…”
Section: Search Strategymentioning
confidence: 99%
“…While Munné et al suggested that by selecting new probe combinations for 10 to 12 chromosomes, FISH could be improved to an accuracy of 89 to 91 % of aneuploidies [26], assessments of a full chromosome complement have to be assumed more accurate.…”
Section: Search Strategymentioning
confidence: 99%
“…Using rehybridization cycles (two to three cycles), 10-12 chromosomes (e.g., X, Y, 13, 18, 21, 16, 17, 18, 15, 22) can be tested and nearly 70-90% of aneuploidies can be detected (Griffi n et al 1991 ;Grifo et al 1992 ;Munné et al 1993 ;Colls et al 2007 ;Munné et al 2010 ) .…”
Section: Chromosome Testingmentioning
confidence: 99%
“…Array CGH (Colls et al 2009;Munne et al 2010) and/or the use of SNP arrays (Handyside et al 2010) could, in theory, be used to do this with great accuracy on a cell by cell basis however using such an approach would be prohibitively expensive in practice. It is more likely that the whole embryo would be assayed by array CGH or SNP haplotyping, thereby neglecting a cell by cell analysis and making any assessment of mosaicism limited.…”
Section: Introductionmentioning
confidence: 99%